Aldehyde Dehydrogenase 1B1 Is Implicated in DNA Damage Response in Human Colorectal Adenocarcinoma - Ilias Tsochantaridis; Alexandros Kontopoulos; Georgia-Persephoni Voulgaridou; Margaritis Tsifintaris; Charisios Triantafyllou; Aglaia Pappa (Cells, 2022)
Aldehyde dehydrogenase 1B1 (ALDH1B1) has been correlated with colorectal tumorigenesis and is considered a potential biomarker for colon cancer. Its expression has been associated with attenuation of the cell cycle in the G2/M phase and resistance to DNA damaging agents. The present study examines the role of ALDH1B1 in DNA damage response (DDR) in human colorectal adenocarcinoma. To this end, we utilized an isogenic HT29 cell line pair differing in the expression of ALDH1B1. The overexpression of ALDH1B1 was related to the translational upregulation of the total and phosphorylated (at ser15) p53. Comet and apoptosis assays revealed that the expression of ALDH1B1 protected HT29 cells from etoposide-induced DNA damage as well as apoptosis, and its overexpression led to increased constitutive phosphorylation of H2AX (at ser139). Furthermore, the expression profile of a variety of DNA damage signaling (DDS)-related genes was investigated by utilizing the RT2 profiler™ PCR array. Our results demonstrated that ALDH1B1 triggered a transcriptional activation of several DNA repair-related genes (MRE11A, PMS1, RAD18 and UNG). Finally, Spearman’s rank correlation coefficient analysis in 531 publicly available colorectal adenocarcinoma clinical samples indicated the statistically significant positive correlation between ALDH1B1 and DDR and repair genes or proteins, such as APEX1, FEN1, MPG, UNG, XRCC1, DDB1, XPC, CIB1, MRE11, PRKDC, RAD50, RAD21, TP53BP1, XRCC6 and H2AX. Collectively, our results suggest that ALDH1B1 may play an essential role in the DDR and DNA repair processes. Further studies on ALDH1B1 will elucidate its precise role in DDR.